In the equation

f(x) = -3( (2-3x^2)^-1/2 + 3x^2(2-3x^2)^-3/2)

my text book jumps to the simplification

f(x) = -6(2-3x^2)^-3/2)

Could someone please explain this simplification?

Printable View

- August 6th 2010, 09:46 PMHefotosSimplifying problem
In the equation

f(x) = -3( (2-3x^2)^-1/2 + 3x^2(2-3x^2)^-3/2)

my text book jumps to the simplification

f(x) = -6(2-3x^2)^-3/2)

Could someone please explain this simplification? - August 6th 2010, 10:20 PMGrandad
- August 6th 2010, 10:28 PMHefotos
Very well explained, thankyou